Reduction of mortality in community-acquired pneumonia after implementing standardized care bundles in the emergency department - Hortmann, Marcus; Popp, Steffen; Lad, Tanuj; Christ, Michael; Heppner, Hans Jürgen (European Journal of Emergency Medicine, 2014)
Objectives: Community-acquired pneumonia (CAP) is associated with high in-hospital mortality. Standardization of diagnostics and adherence to sepsis bundles in the emergency department (ED) are associated with reduced mortality in patients with sepsis. We examined whether introduction of standardized care bundles and checklists in the ED is associated with reduced mortality in patients hospitalized for CAP. Methods: We retrospectively analyzed performance indicators of 2819 consecutive patients with CAP admitted to the Nuremberg Hospital, Germany, from 2008 to 2009. At the turn of the year, CAP care bundles were implemented including interprofessional education, check lists, and institutionalized feedback. Primary endpoint was in-hospital mortality of CAP patients. The secondary endpoint was mortality in the subgroups of CRB-65 risk classes (C, mental confusion; R respiratory rate≥30/min; B systolic blood pressure<90mmHg; 65, age≥65 years). Results: After implementation of CAP care bundles in the ED, in-hospital mortality of affected patients was significantly lower in 2009 compared with 2008 (11.3 vs. 14.3%; P=0.02). Lower mortality was observed in CRB-65 risk classes 2 (n=2142; 11.9 vs. 15.4%, P=0.02) and 3 (n=119; 36.6 vs. 47.9%, P =0.21). Lower in-hospital mortality was also observed in patients between 18 and 79 years (7.2 vs. 10.7%; P=0.02). Mortality in the 80 years and older group was not significantly different after implementation of the CAP care bundle. Antimicrobial therapy was started earlier in the CAP care bundle group (72.8 vs. 82.7% within the first 4h; P=0.0001), and length of stay in the hospital was significantly reduced from 9 to 8 days (P=0.02). Conclusion: This study demonstrated that implementation of standardized CAP care bundles in the ED is associated with a 21% relative risk reduction of in-hospital mortality. Standardization of diagnostic and therapeutic processes in the ED improves outcome of patients hospitalized for CAP.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Antibiotic therapy; Community-acquired pneumonia; CRB-65 risk classes; Emergency department; Reduced mortality; Standardized care